2004
DOI: 10.1111/j.1083-4389.2004.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Teprenone, but not H2‐Receptor Blocker or Sucralfate, Suppresses Corpus Helicobacter pylori Colonization and Gastritis in Humans: Teprenone Inhibition of H. pylori‐Induced Interleukin‐8 in MKN28 Gastric Epithelial Cell Lines

Abstract: Teprenone may modify corpus H. pylori-associated gastritis through its effect on neutrophil infiltration and H. pylori density, in part by its inhibition of IL-8 production in the gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…GGA has also been shown to reduce gastric mucosal myeloperoxidase activity, an indicator of neutrophil infiltration, during restraint stress in an animal experiment. We have also shown previously that 3-month administration of GGA in patients with H. pylori -infected gastritis decreases the activity index and colony density of H. pylori in the corpus of the stomach [18]. Thus, the observation that in this 2-week trial we saw no change in the activity index after GGA treatment indicates that long-term treatment, of at least 3 months duration, is necessary for a reduction in neutrophil infiltration in H. pylori -infected gastritis.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…GGA has also been shown to reduce gastric mucosal myeloperoxidase activity, an indicator of neutrophil infiltration, during restraint stress in an animal experiment. We have also shown previously that 3-month administration of GGA in patients with H. pylori -infected gastritis decreases the activity index and colony density of H. pylori in the corpus of the stomach [18]. Thus, the observation that in this 2-week trial we saw no change in the activity index after GGA treatment indicates that long-term treatment, of at least 3 months duration, is necessary for a reduction in neutrophil infiltration in H. pylori -infected gastritis.…”
Section: Discussionmentioning
confidence: 59%
“…In the case of H 2 RA, there is a lack of histological improvement including neutrophil or mononuclear cell infiltration despite the curative effect of these drugs on gastric mucosal erosions, suggesting that the healing of gastric mucosal lesions is not accompanied by parallel histopathological changes in chronic gastritis [31]. In contrast, recent studies have shown that GGA can suppress gastritis in the human gastric mucosa [18]. An in vitro experiment in gastric mucosal epithelial cells has shown that GGA suppresses the production of interleukin-8, a key player in neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One pharmacological inducer of Hsps is geranylgeranylacetone (GGA). GGA has been safely used in Japan in the clinical treatment of gastric ulcers (Shirakabe et al 1995;Nagasawa et al 1998;Miyake et al 2004;Qian et al 2007). GGA has been shown to induce Hsp70 in variety of tissues, including the gastric mucosa, heart, liver, brain, and cochlea (Hirakawa et al 1996;Ooie et al 2001;Oda et al 2002;Mikuriya et al 2005;Sone et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological actions of GGA include stimulation of the synthesis of gastric mucus and induction of heat-shock proteins (HSPs) [10,11]. GGA induces HSP70 in rat small intestine and prevents ischemia reperfusion injury [12,13].…”
Section: Introductionmentioning
confidence: 99%